2013
DOI: 10.5897/jpbcs12.071
|View full text |Cite
|
Sign up to set email alerts
|

Intra row spacing effect on shelf life of onion varieties (Allium cepa L.) at Aksum, Northern Ethiopia

Abstract: A field experiment was conducted to investigate the influence of intra-row spacing and, variety on yield and shelf life of onion. The study was conducted between August 2010 and April 2011 at Aksum area (Laelay Maichew District). Three different intra-row spacings (5, 7.5 and 10 cm) were evaluated using 4 varieties of onion ('Adama' Red, 'Bombay' Red, 'Melkam' and 'Nasik' Red) using randomized complete block design replicated 4 times. Data on yield and shelf life parameters were recorded and subjected to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
13
10
0
Order By: Relevance
“…This result is in agreement to [36] finding, who reported that highest onion plant leaf length obtained from 10 cm intra-row spacing than at 7.5 cm and 5 cm intra-row spacing at Aksum northern Ethiopia. In agreement with this result, many authors reported that maximum leaf length of onion was recorded in plants spaced at a wider spacing [41,42].…”
Section: Plant Heightsupporting
confidence: 83%
See 1 more Smart Citation
“…This result is in agreement to [36] finding, who reported that highest onion plant leaf length obtained from 10 cm intra-row spacing than at 7.5 cm and 5 cm intra-row spacing at Aksum northern Ethiopia. In agreement with this result, many authors reported that maximum leaf length of onion was recorded in plants spaced at a wider spacing [41,42].…”
Section: Plant Heightsupporting
confidence: 83%
“…Disregarding the effect of N rates, significantly longest onion plants were obtained from intra-row spacing of 15 cm and comparatively shortest plants were observed at intra-row spacing of 7.5 cm which was statistically at par with 10 cm intra-row spacing (Table 2). In agreement to the current finding, author [36] reported tallest onion plant from 10 cm intra-row spacing than plants grown at 7.5 cm and 5 cm at Aksum, northern Ethiopia. Auther [37] also found tallest plant at 25 cm intra-row spacing than at 15 cm intra-row spacing.…”
Section: Plant Heightsupporting
confidence: 79%
“…Sing and Sing (2003) reported that, large size bulbs exhibited the highest weight loss compared to smaller sized bulbs. In agreement with the present result, Kahsay et al (2013) reported that weight loss and rotting of bulbs from the widest spacing (10 cm) and the least spacing (5 cm) were greater than that of the middle one (7.5 cm). Similarly, Bosekeng (2012) (Table 4).…”
Section: Bulb Weight Loss and Bulb Rottingsupporting
confidence: 82%
“…Kahsay et al (2013) observed that as intra-row spacing increased from 5 to 10 cm, marketable bulb yield decreased from 34.49 to 28.1 t ha -1…”
Section: Biological Yield Total Bulb Marketable and Unmarketable Bumentioning
confidence: 96%
“…In most developing countries such as Ethiopia, roads are not adequate for proper transport of horticultural crops, while transport vehicles and other modes, especially those suited for fresh horticultural perishables, are in short supply. Moreover, the extent of losses is significantly influenced by preharvest conditions and field operations such as cultivar and soil types, crop management practices, poor weather conditions, insect pest control programs and harvesting as well as packaging and handling practices [21].…”
Section: Introductionmentioning
confidence: 99%